Heavy Metal contents of sachet Water in Gombe, Nigeria. - Adamu Sani; Yuguda Saleh; Sulaiman Abdulmalik; Tabale P. Raymond; Dahiru S. Mshelia (Ntec Specialist, 2021)
Background: The provision of adequate clean drinking water is a basic human need in every society. In Nigeria, like many developing countries, the provision of clean drinking water is not adequate. The introduction of sachet water is seen by many as a solution to the problem. This is because it is affordable where more than a litter of it is sold at ten Naira or even less. The availability and affordability of sachet water have made it a preferred choice for most people despite questions being raised about the purity and potential toxicity. Objectives: To evaluate the heavy metal contents of sachet water in Gombe, Nigeria. Methodology: Forty samples of sachets water were bought randomly from the streets of Gombe and were analyzed for heavy metals content (lead, cadmium, mercury, arsenic and nickel) using Atomic Absorption Spectrophotometer (AAS). The data obtained were analyzed for frequencies and percentages for qualitative data and minimum and maximum for quantitative data using the system for statistical package for the social sciences (SPSS) version 20.00 for windows. Results: None of the sachet water samples had the date of manufacture or expiry date while about 23% had no National agency for food and drug administration and control (NAFDAC) registration numbers. All the samples had lead levels above the WHO safety limits of 0.01mg/L. Mercury, cadmium and arsenic levels were higher than the safety limits in 23%, 15% and 5% of the samples respectively. No nickel was detected in all the samples. Conclusion: The majority of the sachet water in Gombe is contaminated with heavy metals lead, mercury and cadmium in concentrations above the WHO safety limits. Processes of water purification should be put in place to reduce the heavy metal contents of sachet water in Gombe.